Programmed materials on subject-verb agreement for third year - Ledesma, Milagros M. 1937-
This programmed instructional material is intended to aid and supplement the lesson on English subject-verb agreement to third year high school students. The program is based on the most common errors on English subject-verb agreement committed by students. The programmed text adopted the linear model in which the body of information is broken down into a sequence of small steps called frames.